Oxidative Stability, Affective and Descriptive Sensory Properties of Roasted Peanut Flavored with Oregano, Laurel, and Rosemary Essential Oils as Natural Preservatives of Food Lipids. Issue 5 (2nd April 2019) - Olmedo, Rubén H.; Grosso, Nelson R.
Abstract : The objective of the study is to evaluate lipid oxidation stability in roasted peanuts with essential oils as natural antioxidants. Laurel, oregano, and rosemary essential oil (LEO, OEO, and REO, respectively) provide preliminary antioxidant activity determined by free radical scavenging activity (DPPH test) of 61.1, 58.4, and 47.9% and total phenolic content of 10.3, 10.6, and 8.4 mg g −1 for LEO, OEO, and REO, respectively. Essential oil (EO; 0.02% p/p) is added to roasted peanuts and an affective sensory test (nine‐point hedonic scale) shows that samples with OEO have greater values (6.74) than those of other samples (≈6.20). Chemical (peroxide anisidine diene content and Totox values) volatile (hexanal and 2‐heptenal) and sensory (oxidized and cardboard intensity) indicators change over 84 storage days. Samples with EOs show lower values than those for controls decreasing lipid oxidation. Samples with BHT have the lowest values for deterioration indicators. Principal component analysis of EOs for all indicators and samples with EOs shows that LEO and OEO have better antioxidant properties than REO. Coefficient regression between sensory variables peroxide value and hexanal has a good correlation and can be used as a predictor equation. Essential oils can be used as flavor and natural antioxidant agent in roasted peanut. Practical Applications : The authors believe in the importance of replacing the use of synthetic antioxidants with natural antioxidants in foods. Synthetic antioxidants are being questioned by the perception of safety that these offer by consumers. The essential oils present an antioxidant alternative since their components possess these properties and the application of them is a reason for research to be able to provide more information to the food industry. The sensory properties of essential oils are well received by consumers and the potential for their application as functional flavorings is in its initial stages. That is why this research collaborates with the use of the essential oils of oregano, laurel, and rosemary as possible antioxidants and flavors in peanuts roasted or in other food (which is susceptible to oxidative processes) evidenced its antioxidant properties and the modification of taste and sensory perception by the consumers. Oregano, laurel, and rosemary essential oils can be used as antioxidants in peanut products and foods with high lipid content. Abstract : Oregano, laurel, and rosemary essential oils can be used as antioxidants in peanut products and foods with high lipid content.